Manajemen Kinerja Efektif untuk Mencapai Tujuan Organisasi - Rizal Rizal; Hidayatullah Hidayatullah (Pusat Riset dan Inovasi Nasional, 2025)
Performance management is an important strategy in improving the productivity of individual and team performance in an organization. The purpose of this study is to analyze effective performance management and the factors that influence it, including the role of leadership, technology, communication, and job satisfaction. The research method used is the literature method or library research. The results of this study are that effective performance management not only increases employee work productivity, but also creates a work culture that supports innovation and collaboration. Technology plays an important role in monitoring employee performance in a timely manner, providing fast feedback, and increasing evaluation efficiency. In addition, strong leadership and effective communication are important factors in building high-performance team members. This study confirms that the implementation of the right performance management strategy can increase organizational competitiveness and ensure optimal achievement of long-term goals